Determinação sequencial rápida de As e Sb, Bi e Pb por espectrometria de absorção atômica com geração de hidretos - Batista, Érica Ferreira (2012)
In this study it was developed two systems, one for the fast sequencial determination of As and Sb and other for Bi and Pb using flame atomic absorption spectrometry with hydride generation. To optimize the system for the determination of As (193.7 nm) and Sb (217.6 nm) some variables were evaluated: concentration (in mol L-1) of HCl in the sample and carrier, concentrations (in % w v-1) of KI and NaBH4. For the system used in the determination of Bi (223.1 nm) and Pb (217.0 nm) the following variables were studied: concentration (in mol L-1) of HCl in the sample, concentrations (in % w v-1) of K3Fe(CN)6 and NaBH4. For these studies it was employed Doehlert design to select the best work conditions and obtain more information of the proposed methods. Some analytical parameters were obtained, respectively, for As, Sb, Bi and Pb: Limits of detection (LOD) (0.15; 0.16; 0.60 e 0.77 μg L-1), repeatability (RSD) (1.5; 2.0; 5.9; 6.0 %) and correlation coefficients (r) (0.999; 0.999; 0.998 e 0.997). In order to identify species that could interfere in the determination of As and Sb, Bi and Pb, a study was carried out considering the constituents commonly found in natural waters and chicken feed including Al(III), Co(II), Cr(III), Cu(II), Fe(III), Mn(II), Ni(II) and Zn(II). It was also carried out a study to investigate the influence of the concentration of HNO3 in the As and Sb, Bi and Pb determinations. Through studies with possible interferences, can be observed that there were no significant trend for As, Sb and Bi, the percentage of interference was lower than 21% (contrasts from -4 to 5% for both analytes). In the case of Pb it was noted a strong signal interference by Co (II), Cu (II), Fe (III) and Ni (II) with contrasts varying from -62 % to 29%. The effect of HNO3 concentration was not relevant if it is lower than 10 % v v-1 for As, Sb and 20 % v v-1 for Bi. However, it was noted a strong Pb signal suppression for HNO3 concentrations higher than 0.25 % v v-1. The systems developed were applied in the determination of As and Sb, Bi and Pd in Tietê river water, sea water of Praia Grande Ubatuba, chicken feed and to validate the methods were used two certificate reference materials: Nist 1643e (Trace elements in water) e TMDW-HPS (Trace metals in drinking water).